The Effects of Pancreatic Omentoplasty on Weight Loss, Improvement of Triglyceride and Interleukin-1 Levels in Obese Rats with Type II Diabetes Mellitus Performed Sleeve Gastrectomy - Anggoro Teguh Prasetya; K. Heri Nugroho; Abdul Mughni (HM Publisher, 2023)
Background: Obesity can trigger inflammation or inflammatory disease, which is one of the main features of adipose tissue dysfunction. Adipose secretes several different peptides called adipocytokines, which can induce several pro-inflammatory cytokines such as IL-6, TNF-α, and IL-1. Omentoplasty pancreas dan sleeve gastrectomy is a surgical technique that can treat overweight and metabolic syndrome in obesity and type II DM. This study aims to determine the effect of pancreatic omentoplasty on weight loss and improvement of triglyceride and interleukin-1 levels in rats obesity with type II diabetes mellitus performed sleeve gastrectomy. Methods: This study is an experimental study in vivo. Eighteen rats participated in this study and were grouped into the control group (KI) and the KII and KIII treatment groups. Triglyceride levels were assessed using the spectrophotometric method, and IL-1 levels were assessed using the ELISA method. Data analysis was carried out using SPSS univariate and bivariate. Results: The KII and KIII treatment groups experienced a decrease in body weight, triglyceride levels, and Interleukin-1 levels of rats after the treatment intervention, p<0.05. The KIII treatment group showed the most significant reduction in body weight, triglyceride levels, and Interleukin-1 levels compared to the KII treatment. Conclusion: Pancreatic omentoplasty is effective in reducing body weight, reducing triglyceride levels, and reducing IL-1 levels in obese rats with type II diabetes mellitus undergoing sleeve gastrectomy surgery.